2014
DOI: 10.1002/psc.2618
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus NS5A is able to competitively displace c-Myc from the Bin1 SH3 domainin vitro

Abstract: We studied the interaction of the SH3 domain of Bin1 with a 15-mer peptide of HCV NS5A and show its potency to competitively displace a 15-mer human c-Myc fragment, which is a physiological ligand of Bin1, using NMR spectroscopy. Fluorescence spectroscopy and ITC were employed to determine the affinity of Bin1 SH3 to NS5A(347-361), yielding a submicromolar affinity to NS5A. Our study compares the binding dynamics and affinities of the relevant regions for binding of c-Myc and NS5A to Bin1 SH3. The result gives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The exact function of amphiphysin in viral replication is unclear, but a role in formation or stabilization of the membranous replication structures by means of the BAR ((BIN/amphiphysin/Rvs) domain has been envisaged (9). Moreover, the interaction between HCV NS5A and amphiphysin can contribute to a favorable environment for productive viral replication by inhibiting Bin1-mediated apoptosis (27), possibly due to competitively blocking the binding of Myc to Bin1 (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact function of amphiphysin in viral replication is unclear, but a role in formation or stabilization of the membranous replication structures by means of the BAR ((BIN/amphiphysin/Rvs) domain has been envisaged (9). Moreover, the interaction between HCV NS5A and amphiphysin can contribute to a favorable environment for productive viral replication by inhibiting Bin1-mediated apoptosis (27), possibly due to competitively blocking the binding of Myc to Bin1 (19).…”
Section: Discussionmentioning
confidence: 99%
“…We did not carry out ITC measurements for the HCV NS5A peptide, but based on the slow exchange kinetics observed in NMR titration and its highly similar amino acid composition with CHIKV and SFV, we presume that it also has a similar high amp-SH3 binding affinity. Indeed, a slowly dissociating complex in NMR-based titration experiments and a K d of 0.24 M for the subtype 1b peptide of HCV NS5A ( 347 -TKAPPIPPPRRKRTV 361 ) and amp-SH3 have recently been reported (19).…”
Section: C-terminal Tail Of Dynamin Is Disordered and Binds Amp-sh3 Withmentioning
confidence: 99%
“…This interaction is suspected to play a role in the development of hepatocellular carcinoma in HCV-infected liver cells. In particular, it has been shown that NS5A is able to competitively displace the oncogenic Myc protein from its complex formed with Bin1-SH3 (57). Previously, we have found (37,38) that NS5A displays a high-affinity binding site (PxxP region), as well as two low-affinity binding sites (transient helices H1b and H3) for Bin1-SH3.…”
Section: Ns5a-d2d3 Structural Changes Induced By Bin1-sh3 Bindingmentioning
confidence: 96%
“…Apparently, we are only at the beginning of understanding the complexity of CHIKV HVD interactions with SH3 domain-containing proteins in different cell types and hosts. Interestingly, similarly to NAP1L1, BIN1 was shown to interact with the disordered fragment of hepatitis C virus (HCV)-specific NS5A protein (62,(65)(66)(67). Alteration of this interaction has a negative effect on HCV replication.…”
Section: Fig 11mentioning
confidence: 99%